Teacher prep time in preschools: Children’s best interest - Ólafsdóttir, Sara M.; Hreinsdóttir, Anna Magnea; Björnsdóttir, Margrét S.; Karlsdóttir, Kristín (Menntavísindasvið Háskóla Íslands, 2024)
The status and working conditions for teachers in Icelandic preschools have been a topic of recent discussion. The 2020 agreement with the Association of Preschool Teachers (FL) partly addressed the working conditions for preschool teachers by significantly increasing their preparation time. For example, a full-time preschool teacher serving as a department head now has 10 hours a week for prep—double the five hours allotted previously. Very little research has been undertaken on how preschool teachers’ preparation time is organised and used in Iceland or internationally. The few studies that have been conducted are rather general, focusing more on how much time preschool teachers use to prepare for children’s education, play, and other activities and less on how that prep time is spent. Findings from an Icelandic study on preparation time in preschools indicated that preschool teachers were satisfied with the increased time for preparation but also expressed concern about the corresponding increased absence from the children and their environment. According to Icelandic national curriculum guidelines (Menntamálastofnun, n.d.), play is the essence of preschool practice, and one of the main roles of preschool teachers is to create a learning environment that supports children’s play and encourages their participation and well-being. All children should have equal opportunities to learn through play and interact with others. In these situations, teachers support children and provide them with evocative surroundings. However, research has shown that in daily preschool schedules, play is not given enough space and preschool teachers are often busy with other activities, such as arranging practical plans for teaching practice, leaving behind the important task of observing and supporting children in play. Therefore, this research aimed to explore how preschool teachers use preparation time to improve preschool practices, focusing on children’s rights to be listened to and respected as agents in their own lives. The ...